Nyanyian Adat Masyarakat Desa Longgar: Suatu Pendekatan Hermeneutika - Nita Handayani Hasan (Kapata Arkeologi, 2017)
The existence of folksong is an important thing for the Moluccas. It has functions as an entertainment and the way to deliver the events that existed in the past. This research discuss about jarjinjin and largula folksongs based on hermeneutics approach. The purposes of this research are to transcript and to understand the deepest meaning of the jarjinjin and largula folksongs, and to know the functions of those folksongs for the owner and the young generations. Jarjinjin and largula comes from Longgar village, Kepulauan Aru district, Maluku province. This research use qualitative description method. After transcripted and analyzed  the lyrics, the results show about the history of Longgar, Karey, and Gomu-Gomu village; the folksongs taught the people always remember the message of the ancestors in maintaining brotherhood and culture. For the owner, jarjinjin and largula made brotherhood relation closed beyond the villagers in Longgar, Karey, and Gomu-Gomu village; remaining the history of the ancestors; preservation of local languages; entertaining, because they have sang together and escorting by stampted drums and gongs; and maintaining and preserving the tradition. For young generations, they improved the knowledge about the history of Aru’s ancestors; practicing and demonstrating local language ability; reinforcing love of the history; and maintaining and preserving the tradition.